COVID-19 consent and return to elective orthopaedic surgery: allowing a true patient choice?. (1st September 2020) - Clough, Timothy M.; Shah, Nikhil; Divecha, Hiren; Talwalkar, Sumedh
Abstract : Aims: The exact risk to patients undergoing surgery who develop COVID-19 is not yet fully known. This study aims to provide the current data to allow adequate consent regarding the risks of post-surgery COVID-19 infection and subsequent COVID-19-related mortality. Methods: All orthopaedic trauma cases at the Wrightington Wigan and Leigh NHS Foundation Trust from 'lockdown' (23 March 2020) to date (15 June 2020) were collated and split into three groups. Adult ambulatory trauma surgeries (upper limb trauma, ankle fracture, tibial plateau fracture) and regional-specific referrals (periprosthetic hip fracture) were performed at a stand-alone elective site that accepted COVID-19-negative patients. Neck of femur fractures (NOFF) and all remaining non-NOFF (paediatric trauma, long bone injury) surgeries were performed at an acute site hospital (mixed green/blue site). Patients were swabbed for COVID-19 before surgery on both sites. Age, sex, nature of surgery, American Society of Anaesthesiologists (ASA) grade, associated comorbidity, length of stay, development of post-surgical COVID-19 infection, and post-surgical COVID-19-related deaths were collected. Results: At the elective site, 225 patients underwent orthopaedic trauma surgery; two became COVID-19-positive (0.9%) in the immediate perioperative period, neither of which was fatal. At the acute site, 93 patients underwent non-NOFF trauma surgery, of whom six became COVID-19-positive (6.5%) and three died. A further 84 patients underwent NOFF surgery, seven becoming COVID-19 positive (8.3%) and five died. Conclusion: At the elective site, the rate of COVID-19 infection following orthopaedic trauma surgery was low, at 0.9%. At the acute mixed site (typical district general hospital), for non-NOFF surgery there was a 6.5% incidence of post-surgical COVID-19 infection (seven-fold higher risk) with 50% COVID-19 mortality; for NOFF surgery, there was an 8.3% incidence of post-surgical COVID-19 infection, with 71% COVID-19 mortality. This is likely to have significance when planning a resumption of elective orthopaedic surgery and for consent to the patient. Cite this article: Bone Joint Open 2020;1-9:556–561.